(untitled) (JURNAL KEPERAWATAN, 2025)
Non-hemorrhagic stroke is a disease caused by a narrowing of the blood vessels in the brain resulting in obstructed blood and oxygen flow. Non-hemorrhagic stroke causes facial paralysis, weakness in the arms, difficulty speaking. Treatment of Non Hemorrhagic Stroke clients in a nonpharmacological way that has minimal side effects, one of which is Range Of Motion (ROM) training to increase muscle strength. The purpose of this case study is to describe how the application of Range Of Motion (ROM) exercises to increase muscle strength in patients with impaired physical mobility due to non-hemorrhagic stroke. The method used is descriptive using qualitative research methods. The subjects in this study were two people who suffered from Non Hemorrhagic Stroke. The implementation of Range Of Motion (ROM) exercises is done by measuring the value of muscle strength before and after being given range of motion exercises which are carried out within 20 minutes for 7 consecutive days. The results showed that there was an increase in the 2 subjects, where in the first subject there was an increase in muscle strength value from scale 3 to scale 4 and for the second subject there was also an increase in muscle strength from scale 3 to scale 4. There are changes in increasing muscle strength in the provision of Range Of Motion (ROM) exercises in patients with impaired physical mobility due to Non Hemorrhagic Stroke. Therefore, it is hoped that Range Of Motion (ROM) exercises can be applied as a means in non-pharmacological therapy in patients with Non Hemorrhagic Stroke with physical mobility problems.